2019
DOI: 10.1002/prp2.531
|View full text |Cite
|
Sign up to set email alerts
|

Azelastine potentiates antiasthmatic dexamethasone effect on a murine asthma model

Abstract: Glucocorticoids are among the most effective drugs to treat asthma. However, the severe adverse effects associated generate the need for its therapeutic optimization. Conversely, though histamine is undoubtedly related to asthma development, there is a lack of efficacy of antihistamines in controlling its symptoms, which prevents their clinical application. We have reported that antihistamines potentiate glucocorticoids’ responses in vitro and recent observations have indicated that the coadministration of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Lung sections were assessed for severity of inflammation by two independent observers, Dr. María Virginia Gentilini and Dr. Carlos Bueno, blinded to treatment. An index of pathologic changes in hematoxylin and eosin (H&E) slides was obtained accordingly to Zappia et al (2019). Briefly, 20 consecutive airways per slide were examined at 400 × magnification and scoring the inflammatory infiltrates around the airways and vessels for severity (0, normal; 1, ≤3 cells diameter thick; 2, 4 to 10 cells diameter thick; 3, ≥10 cells diameter thick).…”
Section: Pulmonary Infection In Mouse Modelmentioning
confidence: 99%
“…Lung sections were assessed for severity of inflammation by two independent observers, Dr. María Virginia Gentilini and Dr. Carlos Bueno, blinded to treatment. An index of pathologic changes in hematoxylin and eosin (H&E) slides was obtained accordingly to Zappia et al (2019). Briefly, 20 consecutive airways per slide were examined at 400 × magnification and scoring the inflammatory infiltrates around the airways and vessels for severity (0, normal; 1, ≤3 cells diameter thick; 2, 4 to 10 cells diameter thick; 3, ≥10 cells diameter thick).…”
Section: Pulmonary Infection In Mouse Modelmentioning
confidence: 99%
“…To assess the therapeutic effect of G-F1, mice were administered with an intraperitoneal injection of 50 mg/kg G-F1 or an intranasal injection of 3.5 mg/kg G-F1 three times a week during CRS modeling. Dexamethasone (Sigma-Aldrich) was used as a positive control at a dosage of 2 mg/kg intranasally as described in previous studies using murine model of ECRS and asthma [ 36 , 37 ]. After CRS development and treatment, nasal tissue sections were trimmed from euthanized mice and placed in 4% formaldehyde solution (Thermo Fisher Scientific, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…We discussed that the existence of cell types co-expressing H1R and GR suggests that our findings may have implications for regulation of inflammation in several systems, and the co-administration of corticoids and antihistamines could result in a reduction of the GC dose needed to achieve a therapeutic effect. As a proof-of-concept, we demonstrated an effective use for the treatment of asthma in an experimental murine model [25]. However, there is a need for a careful evaluation of the side effects of antihistamine and GC co-administration, because GCs' undesired effects could also be enhanced by antihistamines [26].…”
Section: Introductionmentioning
confidence: 95%
“…We have previously shown that the antihistamines mepyramine (MEP) and azelastine (AZE) potentiate dexamethasone (DEX) inhibition of NF-κB activity in vitro on an IL-6 promoter-driven luciferase reporter [24,25]. To extend this study we evaluated the effect of the different antihistamines mepyramine (MEP), trans-triprolidine (TRIP), cetirizine (CET), chlorpheniramine (CHLOR) and diphenhydramine (DIPH) using HEK-293T cells cotransfected with plasmids coding for GR, H1R and the aforementioned reporter.…”
Section: Antihistamines Enhance Dexamethasone-mediated Inhibition Of Nf-κb Activity Induced By Tnf-αmentioning
confidence: 99%